2022
DOI: 10.3390/diagnostics12071560
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Methotrexate Pathway in Rheumatoid Arthritis Patients: Approach toward Personalized Medicine

Abstract: Background: Methotrexate (MTX) is one of the most common medications used for rheumatoid arthritis (RA) treatment. Single-nucleotide polymorphisms (SNPs) could potentially predict variability in therapeutic outcomes. Aim: This study aims to assess the impact of SNPs in genes encoding for the MTX pathway for predicting clinical and therapeutic responses to MTX in a cohort of Egyptian patients with RA. Subjects and Methods: Data from 107 Egyptian RA patients (aged 44.4 ± 11.4 years) treated with MTX monotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been proposed that the RFC1 G80A variation in exon 2 is linked to the effectiveness of MTX. It causes the replacement of histidine for arginine at amino acid position codon 27 in the first transmembrane domain of the RFC1 protein [ 19 ]. A previous study done in silico showed that this variant changed the topology of RFC1 at the S1, S2, S4, S8, S9, and S10 transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the RFC1 G80A variation in exon 2 is linked to the effectiveness of MTX. It causes the replacement of histidine for arginine at amino acid position codon 27 in the first transmembrane domain of the RFC1 protein [ 19 ]. A previous study done in silico showed that this variant changed the topology of RFC1 at the S1, S2, S4, S8, S9, and S10 transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%